The Dynamics of Tafsir bi al-Ra'y: Exploring Rational Methods in Qur'anic Interpretation: Dinamika Tafsir bi al-Rayi: Mengupas Metode Rasional dalam Penafsiran al-Qur’a - Diany Mumtaz Hanifiah; Yogi Muldani Hendrawan; Eni Zulaiha (Tunas Harapan Ummat Foundation, 2025)
This journal explores one of the methods of Quranic exegesis, namely tafsir bi al-ra'yi, a method that has been the subject of extensive debate among scholars and involves specific limitations that must be observed when interpreting the Qur'an. Tafsir bi al-ra'yi is an approach that relies on rationality and ijtihad (independent reasoning) in interpreting the Qur'an. It is characterized using intellect to comprehend Quranic verses while considering linguistic context, the reasons for revelation (asbabun nuzul), and the principles of Islamic law (sharia). This method has generated significant discourse within the field of Quranic interpretation, with both supporters and critics. To provide a comprehensive foundation for this discussion, this paper includes an overview of the definition and historical development of tafsir bi al-ra'yi. The aim of this research is to analyze the boundaries, conditions, and principles that must be followed by an interpreter when employing the tafsir bi al-ra'yi method, in order to prevent deviations from the Qur'an's original meaning